The “right to repair” – possible implications for the labour market - Thobe, Ines [Verfasser]; Eckermann, Frauke [Verfasser]; Maier, Tobias [Verfasser] (My University, 2023)
"In March 2023, the European Commission presented a proposal for a directive on a “right to repair”. The aim is for consumers to be able to use products for longer, thus leading to greater resource efficiency in the interests of a circular economy. This article uses a scenario analysis to investigate what implications different repair behaviour and longer duration of use will have for the labour market, the areas in which job shifts will occur between sectors and occupations, and what this will mean in terms of securing a supply of qualified skilled workers." (authors' abstract; BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; G 1.2 Arbeitsmarkt; 370; 330; Verbraucherschutz; Instandhaltung; Kreislaufwirtschaft; Abfallvermeidung; Rechtliche Regelungen; Auswirkung; Beschäftigungseffekte; Arbeitsmarktentwicklung; Szenario